Diseño de un programa de reducción de residuos sólidos en la fuente para el colegio La Toscana Sede A (2021)
The aim of this work is to contribute from an educational institution where high school students between 13 and 18 years old and other communities are present to the global problem of solid waste, designing a program to reduce it from the source for the school “La Toscana Sede A”